The Emerging Role of N6-Methyladenosine RNA Methylation as Regulators in Cancer Therapy and Drug Resistance - Chen, Zhaolin; Hu, Ying; Jin, Le; Yang, Fan; Ding, Haiwen; Zhang, Lei; Li, Lili; Pan, Tingting (Frontiers in Pharmacology, 2022)
N6-methyladenosine (m6A) RNA methylation has been considered as the most prevalent, abundant and conserved internal transcriptional modification throughout the eukaryotic mRNAs. Typically, m6A RNA methylation is catalyzed by the RNA methyltransferases (writers), is removed by its demethylases (erasers) and interacts with m6A-binding proteins (readers). Accumulating evidence shows that abnormal changes in the m6A levels of these regulators are increasingly associated with inflammatory processes, mainly through stimulation of anti- or pro-inflammatory cytokines. However, the molecular mechanisms underlying m6A RNA methylation in inflammatory cancer and cancer-associated inflammation have not been comprehensively clarified. Herein, we review the recent findings on biological regulation of m6A RNA methylation and summarize its potential therapeutic strategies in both inflammation and cancer.